Geometrical and trigonometric optics - Dereniak, Eustace L. (Knovel Library., 2008)
Optics has recently evolved into one of the most flourishing fields in physics, with photonics finding increasing application in products such as optical thermometers, camera monitors and LED lighting, plus numerous military applications.